Impact of hot isostatic pressing on microstructures of CMSX-4 Ni-base superalloy fabricated by selective electron beam melting. (15th November 2016) - Ruttert, B.; Ramsperger, M.; Mujica Roncery, L.; Lopez-Galilea, I.; Körner, C.; Theisen, W.
Abstract: Selective electron beam melting (SEBM) is a powder-bed-based additive manufacturing process that was used to produce cylindrical and columnar-grained parts made of Ni-base superalloy CMSX-4 from pre-alloyed and atomized powder. SEBM is characterized by high temperature gradients during solidification, which results in a very fine microstructure that is several orders of magnitude smaller than in conventionally cast material. This opens up new perspectives regarding time-consuming solution heat treatment. Nevertheless, microstructural heterogeneities, such as segregation and porosity, are still present on a much smaller scale, and also the high susceptibility to cracking of this alloy class during welding has to be taken into account. Since the latest generation of hot isostatic presses (HIP) are able to simultaneously heat-treat and eliminate porosity owing to their quenching capability, such a HIP is used in this work. The influence of different HIPing-heat-treatment-strategies with variation of temperature and time at a constant pressure on the SEBM-microstructure was investigated with emphasis primarily on segregation and porosity. The results demonstrate that only a few minutes of solutioning are sufficient to dissolve segregations and to close pores. The initial degree of homogeneity of the SEBM-material is responsible for the short solutioning-time. Graphical abstract: Highlights: Selective electron beam melting is used for the fabrication of Ni-base superalloy material. Subsequently a novel hot isostatic press with the ability to quench was utilized for the homogenization heat treatment. The microstructures after additive manufacturing and also after hot isostatic pressing were characterized. Promising, defect free microstructures are thus generated combining these advanced processing routes.